The Use of Mo Lam Song LocaL Wisdom For Holistic Health Care in Khamsri Village, Nongkungsri District, Kalasin Province, Thailand - Anuson, Artit; Pheangsoi, Kosit (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2019)
The objectives of the research article were 1) study the history of Mo Lam Song, 2) study about the superstition and the local wisdom for holistic health care from the past to the present, and 3) investigate the use of Mo Lam Song local wisdom for holistic health care. We have chosen the northeastern-style singer in Kamsri village, Nongbuasubdistrict, Nongkungsri district, Kalasin province which is the only one place in Thailand that inherits the tradition of Mo Lam Song. The sample group of informants that gives the information to the researcher using by interview method consists of 1) 10 persons of Key Informants group, 2) 30 persons of Causal Information group; Is a group that provides in-depth information That is the knowledge about Mo Lam Song And holistic health guidelines for self-reliant communities, 3) 10 persons of General Information group. The tools used in the research are Preliminary survey, observation form, interview form and group discussion, Data collection from documents and field data collection, Data analysis from the study and data collection by writing data analysis with the descriptive analysis and separate the proposal according to the purpose of the research. The results show that 1) the history of Mo Lam Song worship at Kamsri village has been inheriting since the ancestors until now. Ones need to believe in the spirit, the godness and the guardian spirit and also make the worship to keep contact with them. This will help in any obstacles, especially, the sickness. 2) For the belief and the local wisdom for holistic health care from the past to the present, the community still believes in the spirit and god. In order to numb the pain from the sickness, in the past, they needed the helps from those spirits. Although there is the modern medicine to assist in the precise diagnosis in the present but for some diseases that cannot be treated, it is necessary to rely on the worship which helps in the sickness and also encourages the patient. 3) the use of Mo Lam Song local wisdom for holistic health care in that area aims to encourage people in living along with the culture and tradition created by the ancestors. It has been perfectly guided with the sociality, the nature, the environment, and the spirit by ones who have the same culture and belief in order to preserve the tradition. The local wisdom for health care based on musical worship along with the superstition of spirit, soul and god is the way to morale and encourage people in that area in cherishing their own culture rising to their strength.